Management of Malaria in Children Younger Than 5 Years Old During Coronavirus Disease 2019 Pandemic in Sierra Leone: A Lesson Learned? - Buonsenso, Danilo; Iodice, Francesco; Cinicola, Bianca; Raffaelli, Francesca; Sowa, Solia; Ricciardi, Walter (Frontiers in Pediatrics, 2021)
Growing evidences are showing the potential indirect effects of the Coronavirus Disease 2019 (COVID-19) on the health systems of low-resource settings, where diseases such as Tuberculosis, Human Immunodeficiency Virus (HIV) and Malaria represent major killers. Therefore, we performed a retrospective study aimed to evaluate the impact of COVID-19 on Malaria programs in a peripheral region of Sierra Leone, previously involved by the Ebola outbreak in 2015, when malaria care have been impaired since local health systems were overwhelmed by Ebola cases. During COVID-19 in Sierra Leone, we did not notice a significant drop in malaria diagnosis in children, suggesting that a proactive approach in the management of malaria in endemic countries during COVID-19 may have had a positive impact. A comprehensive approach that include also educational activities to sensitize the local population, was useful to guarantee successful malaria diagnosis and treatment, and prevents excess of malaria deaths due to potential disruption of the local health systems related to the SARS-CoV-2 pandemic.